USING CHILDREN TO SELL: CHILDHOOD AND ADVERTISING OF CONSUMER MAGAZINES - Paula Deporte Andrade; Marisa Vorraber Costa (Editora da Universidade de Santa Cruz do Sul, 2010)
In the present society, also identified as a "consumer society" (Bauman, 2008), people, irrespective of gender, age, social and financial conditions, are all called for consumption. In this article we turn to the childhood and approached one of the faces of their insertion into the society of consumers, trying to show how children are used to sell. As a frame of theoretical reference we adopt, among others, the writings of Zygmunt Bauman, Juliet Schor and Robert Bocock, dealing with contemporary versions of consumption. Analyzing weekly magazines of large circulation, we discuss how productive it is for the economic market the alliance between childhood and consumption and we argue that this use of children in publicity contributes for a new conception of childhood: the childhood of consumption. An erotized childhood, always wanting more and never feeling satisfied, focused in acquiring and showing off. This is the childhood that is coming to school with new interests, preferences and behavior, deserving our entire attention. Key-words: contemporary childhood, childhood and consumption, consumer society, advertising, magazines.